DOMINUS LITIS PADA KOMISI NASIONAL HAK ASASI MANUSIA DALAM PENEGAKAN HAK ASASI MANUSIA DI INDONESIA - Suardita, I Ketut; PRATAMA, I PUTU ANDIKA; Sukmayanti, Made Sinthia (Fakultas Hukum Universitas Ngurah Rai, 2024)
The national human rights commission is one of the independent institutions in Indonesia, which is responsible for the enforcement of human rights. In carrying out its functions in the enforcement of human rights, the national human rights commission collaborates with the prosecutor's office because the national human rights commission only discusses the settlement up to the investigation process, and the next process in justice (dominus litis) is carried out by the prosecutor's office. This research intend to understand the role regulation at the national human rights commission, as well as to understand the importance of regulating the role of the dominus litis. This research uses normative legal research methods, by reviewing the laws and regulations relating to the problem. Furthermore, it can be explained about the regulation of the role of dominus litis in the unregulated national commission, because the function of the dominus litis is still under approval by the prosecutor's office. The regulation of the dominant role in the national human rights commission has a very important role in emphasizing the functions and objectives and clarifying the independence of the national human rights commission.